2016
DOI: 10.14738/assrj.312.2379
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Using Blackboard in Improving the English Listening and Speaking Skills of the Female Students at the University of Hail

Abstract: The use of Learning Management Systems (LMSs) in Saudi universities has brought about significant changes in the academic environment. Therefore, the effectiveness of these systems deserves a careful examination. The current study investigates female students' perceptions on the accessibility, usability and effectiveness of using Blackboard (Bb) in a web-enhanced listening and speaking course at the University of Hail (UoH). The study was conducted during the first semester of the academic year 2015-16. Data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 8 publications
0
26
1
Order By: Relevance
“…A lack of practice, specifically when there are limited opportunities to interact in English, is perhaps one reason why many researchers have found that EFL learners' speaking abilities are often quite low compared to their listening, reading, and writing skills (Al-Jabry, Salahuddin, & Al-Shazly, 2014;Hamouda, 2020;Hussein 2016). Hussein (2016) and others (Al-Jabry et al, 2014) have suggested that the limited opportunities for learners to practice speaking may be one of the explanations for learners' relatively low speaking abilities Virtual EFL classrooms and online learning (also known as e-learning) offer a potential solution to these and other challenges. Virtual classrooms can enable learners' interactions with teachers as well as between the learners themselves.…”
Section: Literature Review Second Language Learning In Virtual Classrmentioning
confidence: 99%
See 1 more Smart Citation
“…A lack of practice, specifically when there are limited opportunities to interact in English, is perhaps one reason why many researchers have found that EFL learners' speaking abilities are often quite low compared to their listening, reading, and writing skills (Al-Jabry, Salahuddin, & Al-Shazly, 2014;Hamouda, 2020;Hussein 2016). Hussein (2016) and others (Al-Jabry et al, 2014) have suggested that the limited opportunities for learners to practice speaking may be one of the explanations for learners' relatively low speaking abilities Virtual EFL classrooms and online learning (also known as e-learning) offer a potential solution to these and other challenges. Virtual classrooms can enable learners' interactions with teachers as well as between the learners themselves.…”
Section: Literature Review Second Language Learning In Virtual Classrmentioning
confidence: 99%
“…Virtual classrooms can enable learners' interactions with teachers as well as between the learners themselves. Indeed, much of the recent research in the EFL domain has attended to the possible benefits of virtual learning environments for English learners (Bianchi, Yyelland, Yang & McHarg, 2019;Hamouda, 2020;Hussein, 2016;McBrien, Cheng, & Jones., 2009). Nevertheless, along with the potential utility of e-learning environments, it is also important to carefully consider whether online learning environments can be as effective as traditional classrooms (Hamouda, 2020).…”
Section: Literature Review Second Language Learning In Virtual Classrmentioning
confidence: 99%
“…Both these studies have given evidence of a positive attitude held by the Saudi Faculty and the students towards the Blackboard LMS. Besides, there are also other studies (Hussein, 2011;Al-Khalifa, 2012;Choudhury, 2015;Hussein, 2016) which have examined various other variables with respect to Blackboard and online LMSs in Saudi Arabia universities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Researchers focused on attitudes and perceptions (Al Zumor et al, 2013;Ja'ashan, 2015;Alaidarous & Madini, 2016) and as improving listening and speaking skills (Hussein, 2016).…”
Section: Review Of Literaturementioning
confidence: 99%